Organizational Correlates of a Management by Objectives Program - Shetty, Y. K.; Carlisle, Howard M. (Academy of Management Journal, 1974)
The article provides information on a study which applied and evaluated the concept of management by objectives (MBO) in an academic environment. It reports on the results of an in-depth questionnaire administered to participating faculty members after the MBO program has been in progress for one academic year, including the reactions of participating faculty members to an MBO program and the assessment of the degree of variation in the reactions based on differences in professional rank, status of tenure, length of services and academic discipline. According to the author, the results showed that the MBO program did not create significant differences in the tenure system.